TEACHERS’ METHODS TO FOSTER CRITICAL THINKING OF PRIMARY STUDENTS THROUGH EVALUATIVE READING - Andika , Jeffri Dian (UICELL, 2023)
Critical thinking is an essential skill that students, especially primary students, must acquire early. It helps the students to make sense of the world around them and to communicate their ideas. Primary students who learn English in their schools have been exposed to English text for their lessons. Abundant research has proven that reading activities, especially evaluative reading, can generate students' critical thinking with their teacher's guidance. Teachers have used different methods in evaluative reading and caused different impacts on students. This article analyses the most effective method in evaluative reading to foster critical thinking for primary students. The data are collected from existing journal articles, proceeding papers from conferences, books, and theses. By analyzing existing research findings and empirical evidence, this study examines teachers' different methods to foster critical thinking in primary students through evaluative reading. It describes the strengths, challenges, and opportunities after implementing various methods through evaluative reading. This study's findings give an overview related to the use of various methods of evaluative reading to foster critical thinking in primary students and practical insights for teachers in primary education. Keywords: Critical Thinking, Evaluative Reading, Primary Students, Teachers